A contribution to the pollen morphology of the Cryptocarya group (Lauraceae). Issue 3 (4th May 2018) - Rohwer, Jens G.
Abstract: In this study, pollen grains of 74 taxa (84 specimens) of the Cryptocarya group, including 22 type collections, have been examined by scanning electron microscopy. Pollen grains of Aspidostemon, Endiandra, Hexapora, Potameia and Triadodaphne are described here for the first time. For the other genera ( Beilschmiedia, Cryptocarya, Eusideroxylon, Potoxylon ) the results of previous studies are largely confirmed, but a novel type of exine covered by clavate-baculate structures was found in a few Cryptocarya species ( C. gracilis and C. macrodesme from New Caledonia, C. saligna from South America). A larger diversity of spinule morphology and density than hitherto known is documented among the African species of Beilschmiedia .